Reevaluating plantation commodities for sustainable economic growth in Balantak District, Banggai Regency - Puspapratiwi, Dian; Djamaluddin, Ismail; Maudara, Akbar; Zaenuddin, Ruslan A.; Katili, Hidayat Arismunandar (Fakultas Pertanian Universitas Yudharta Pasuruan, 2025)
Introduction: The plantation sub-sector is one of the agricultural sectors that occupies an important position in supporting the regional economic order, especially the Banggai Regency area because it is a source of raw materials for the feed and clothing industry. So, it was carried out to evaluate community income on plantation commodities in Balantak District. Methods: This research uses quantitative descriptive analysis method with Location Quotient and Shift Share Analysis approach and income analysis. Results: The results obtained are the superior commodity of plantation crops in Balantak District obtained 2 types of plants, namely clove and nutmeg plants, with LQ values greater than one (> 1) and positive SSA (+). Clove crops are found in 7 villages, namely Talima A village, Talima B village, Balantak, Luok village, Boloak village, Dale-Dale, and Talang Batu village. Furthermore, Nutmeg plants are found in 3 villages/sub-districts, namely, Dolom village, Padang village, and Mamping village. Furthermore, the income analysis of superior plantation crops, namely cloves and nutmeg in Balantak sub-district, obtained a value of 1.5 with the criteria of R/C ratio> 1, which means that farming is profitable and feasible to develop in Balantak District. Conclusion: The results of this study form the basis of recommendations for local governments to manage and focus more on superior plantation crops that can support economic growth in Balantak District, Banggai Regency.